2005
DOI: 10.1007/s00221-005-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency rTMS effects on sensorimotor synchronization

Abstract: Previous studies using low frequency (1 Hz) rTMS over the motor and premotor cortex have examined repetitive movements, but focused either on motor aspects of performance such as movement speed, or on variability of the produced intervals. A novel question is whether TMS affects the synchronization of repetitive movements with an external cue (sensorimotor synchronization). In the present study participants synchronized finger taps with the tones of an auditory metronome. The aim of the study was to examine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
(57 reference statements)
3
20
3
Order By: Relevance
“…The tapping accuracy, as judged by the position of the finger at the time of the metronome click, was slightly improved by TMS at low intensities. Although this is unexpected, it is in line with recent observations of Doumas et al (2005) that motor cortex inhibition decreased the tap-tone asynchrony (tapping inaccuracy).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The tapping accuracy, as judged by the position of the finger at the time of the metronome click, was slightly improved by TMS at low intensities. Although this is unexpected, it is in line with recent observations of Doumas et al (2005) that motor cortex inhibition decreased the tap-tone asynchrony (tapping inaccuracy).…”
Section: Discussionsupporting
confidence: 89%
“…Figure 3 displays the percentage of accurate taps for both the unperturbed baseline and for the TMS perturbations (two left columns). TMS does not reduce the accuracy of tapping and, on the contrary, a slight increase is observed (see also Doumas et al, 2005), although the difference is not statistically significant (one tailed t test, p = .15). Interestingly, tapping accuracy remained high also when the finger performed stalls and doubles (see Figure 4, left-most columns).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Doumas, Praamstra, and Wing (2005) found that while disruption of contralateral PMC by rTMS altered neither the NMA nor error correction after a phase shift, disruption of the contralateral motor cortex reduced the magnitude of NMA (i.e., taps fell closer to the tones). The less negative asynchronies as a result of motor cortical inhibition were interpreted as being due to either a slowdown of the timekeeper process, which lengthened the internally measured period, or to a reduced sensitivity of motor cortex to the somatosensory input.…”
Section: Asynchrony and Error Correctionmentioning
confidence: 89%